Thermodynamic modeling and Exergy Analysis of Gas Turbine Cycle for Different Boundary conditions - Lalatendu Pattanayak (Institute of Advanced Engineering and Science, 2015)
In this study an exergy analysis of 88.71 MW 13D2 gas turbine (GT) topping cycle is carried out. Exergy analysis based on second law was applied to the gas cycle and individual components through a modeling approach. The analysis shows that the highest exergy destruction occurs in the combustion chamber (CC). In addition, the effects of the gas turbine load and performance variations with ambient temperature, compression ratio and turbine inlet temperature (TIT) are investigated to analyse the change in system behavior. The analysis shows that the gas turbine is significantly affected by the ambient temperature which leads to a decrease in power output. The results of the load variation of the gas turbine show that a reduction in gas turbine load results in a decrease in the exergy efficiency of the cycle as well as all the components. The compressor has the largest exergy efficiency of 92.84% compared to the other component of the GT and combustion chamber is the highest source of exergy destruction of 109.89 MW at 100 % load condition. With increase in ambient temperature both exergy destruction rate and exergy efficiency decreases.